Psychological well-being and incident frailty in men and women: the English Longitudinal Study of Ageing. - Gale, C; Cooper, C; Deary, I; Aihie Sayer, A (Cambridge University Press, 2014)
BACKGROUND: Observations that older people who enjoy life more tend to live longer suggest that psychological well-being may be a potential resource for healthier ageing. We investigated whether psychological well-being was associated with incidence of physical frailty. METHOD: We used multinomial logistic regression to examine the prospective relationship between psychological well-being, assessed using the CASP-19, a questionnaire that assesses perceptions of control, autonomy, self-realization and pleasure, and incidence of physical frailty or pre-frailty, defined according to the Fried criteria (unintentional weight loss, weakness, self-reported exhaustion, slow walking speed and low physical activity), in 2557 men and women aged 60 to ≥ 90 years from the English Longitudinal Study of Ageing (ELSA). RESULTS: Men and women with higher levels of psychological well-being were less likely to become frail over the 4-year follow-up period. For a standard deviation higher score in psychological well-being at baseline, the relative risk ratio (RR) for incident frailty, adjusted for age, sex and baseline frailty status, was 0.46 [95% confidence interval (CI) 0.40-0.54]. There was a significant association between psychological well-being and risk of pre-frailty (RR 0.69, 95% CI 0.63-0.77). Examination of scores for hedonic (pleasure) and eudaimonic (control, autonomy and self-realization) well-being showed that higher scores on both were associated with decreased risk. Associations were partially attenuated by further adjustment for other potential confounding factors but persisted. Incidence of pre-frailty or frailty was associated with a decline in well-being, suggesting that the relationship is bidirectional. CONCLUSIONS: Maintaining a stronger sense of psychological well-being in later life may protect against the development of physical frailty. Future research needs to establish the mechanisms underlying these findings.